Housing - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2018)
This book is proposed as both a general reading of the discipline for students in architecture and urban planning, and offers a variety of materials for professionals of local and international organizations. It brings together studies with new perspectives and relevant subjects from different geographical areas. The book gathers the contributions of international researchers and experts. It is divided into three parts and eight chapters: Part I, "Introduction to Housing Affairs," includes a chapter that discusses a general reading of housing as meaning and action in social, economic, and environmental city life. Part II, "Case Studies Upon Housing Policies," includes four chapters. It consists of many examples from different geographical areas and domains. Part III, "Housing Quality and Affordability," includes three chapters; housing quality, sustainability, and development are the main subjects for this part.